Effect of the pre-magnetic treatment of seeds and the N-fertilizer on the yield and quality of groundnut grown in sandy soil - Ahmed, Marwa A.; Shaheen, Alaa A.; Shaban, Khaled A. H.; T. Rashad, Rama (Universitas Sebelas Maret, 2023)
This field trial aimed to study the effect of the magnetic treatment (MT) of urea as a nitrogen (N) fertilizer as well as the MT of the groundnut (Arachis hypogaea L.) seeds before sowing on the crop yield and quality under sandy soil conditions during the summer seasons of 2020 and/or 2021. Treatments were distributed in a split-plots design in triplicates. The control CL has received the recommended dose RD of the N-fertilizer while other treatments received the rates 50, 75, and 100% of the RD as magnetized urea (main factor F1) applied to the surface soil. The sub-factor (F2) was the time of MT (15, 30, and 45 min) of the groundnut seeds exposed to magnetic field MF 1.4 T before planting. Representative samples from the soil and plant were taken after harvesting. At the 15-min time and 100% N-fertilization, the yield of pods and seeds (kg ha-1) has increased relatively by 8.2% and 9.7% respectively, compared to the corresponding CL. At the 30-min time and 50% and 100% N-fertilization, the yield (kg ha-1) has increased relatively by 9.7% and 13.3% respectively for pods and by 10.1% and 16.8% respectively for the seeds. At the 45-min time and 50% N-fertilization, the yield (kg ha-1) has increased by 12.4% and 14.6% for pods and seeds, respectively. The 100% N-fertilization along with 15 min MT before cultivation or the 50% and/or 100% N-fertilization along with 30 min MT or the 50% along with 45 min MT could be recommended. The agronomic efficiency (AE) for the N, P, and K nutrients was increased by the MT in the order 15 min < 30 min < 45 min at the 50, 75, and 100% N-fertilization rates.